(untitled) (Bangladesh Journal of Medical Microbiology, 2026)
Background: Gram-negative bacteria are a common cause of infections in burn patients, and a major cause of nosocomial wound infection. Objective: The purpose of the present study was to isolate and identify gram-negative bacteria from both burn wounds and the environment of burn wards, and to detect their antimicrobial resistance pattern at Dhaka Medical College Hospital (DMCH). Methodology: This cross-sectional study was conducted in the Department of Microbiology at Dhaka Medical College, Dhaka, Bangladesh from the period January to December, 2016. Burn swabs were collected from patients admitted in burn unit of DMCH, and environmental samples were collected from various areas of burn unit. Samples were cultured in blood agar and MacConkey’s agar media. Organisms were identified by colony morphology and biochemical tests. Antimicrobial susceptibility was done by Kirby Bauer disc diffusion method. ESBL-producing organisms were identified by Double Disc Synergy test. Results: Out of 300 burn wounds, 294 (98%) were culture positive. Among 294 (98%) organisms, the most prevalent was Pseudomonas aeruginosa (43.19%), followed by Klebsiella species (17.68%), Proteus species (13.94%), and others. Out of 200 environmental samples, 37 (18.50%) yielded growth in culture. Among them, Pseudomonas aeruginosa was (44.82%), followed by Escherichia coli (20.68%), Klebsiella species and Acinetobacter species (13.79%), and Citrobacter species (6.89%). Among the isolated gram-negative organisms from burn wound the highest resistance observed were Pseudomonas aeruginosa to Ceftazidime (86.61%), Klebsiella species to ciprofloxacin (92.30%), Proteus species to amikacin (95.12%), Escherichia coli to Ciprofloxacin (92.31%) Enterobacter species and Citrobacter species both to cefuroxime and Acinetobacter species to gentamicin (92.3%). All the gram-negative organisms were highly sensitive for colistin except Klebsiella species where imipenem was most sensitive. Antibiotic resistance pattern is not statistically significant between Pseudomonas aeruginosa isolated from burn wounds and environmental samples. Only isolated gram-positive organism was Staphylococcus aureus (1.36%). Among the isolated gram-negative bacteria, 85 (29.31%) and 7 (24.13%) were ESBL producers, isolated from clinical samples and environmental samples, respectively. Conclusion: This study provides insight into the emergence of multidrug resistant organisms in both clinical and environmental samples. Pseudomonas aeruginosa is the most prevalent organism isolated from clinical samples. The finding also suggested environment as a reservoir of various gram-negative organisms for infections in burn patients. Bangladesh Journal of Medical Microbiology, July 2025;19 (2):121-128